Management Background, Intellectual Capital and Financial Performance of Indonesian Bank - Elizabeth Hutami Widowati; Noel Singgih Haryo Pradono (KINERJA, 2017)
This research aims to determine the effect of management background which proxy by accounting education background, MBA education background, Chinese ethnicity and intellectual capital (VAIC) on conventional banks’ financial performance (ROA) in Indonesia. The Population consists of all conventional banks listed on Indonesia Stock Exchange period of 2012 to 2015. Using purposive sampling method to screen the data, the final sample for this research is 140 data that consists of 39 banking companies. This research used Eviews7 software to conduct panel data regression analysis. The results showed that accounting education background and Chinese ethnicity are not significantly affect financial performance. Meanwhile MBA education background and VAIC are significantly affecting financial performance (ROA).Keywords: management background, VAIC, ROA, banking.